2008
DOI: 10.1128/aem.00972-08
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Crenarchaeota Representatives in Terrestrial Hot Springs of Russia and Iceland

Abstract: Culture-independent (PCR with Crenarchaeota-specific primers and subsequent denaturing gradient gel electrophoresis) and culture-dependent approaches were used to study the diversity of Crenarchaeota in terrestrial hot springs of the Kamchatka Peninsula and the Lake Baikal region (Russia) and of Iceland. Among the phylotypes detected there were relatives of both cultured (mainly hyperthermophilic) and uncultured Crenarchaeota. It was found that there is a large and diverse group of uncultured Crenarchaeota tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Recent molecular analyses indicate that A. sulfurireducens (Crenarchaeota, Acidilobales) is a numerically dominant organism in acidic, high-temperature YNP springs (11,33), and closely related strains of Acidilobales have been detected in acidic terrestrial geothermal environments around the world (13,18,34). Previous microscopic analyses of batch cultures of A. sulfurireducens growing in pH 3.0 medium containing ␣-S 8 as the sole TEA indicated that the majority of cells were planktonic and not associated with large elemental sulfur particles during sulfurdependent growth (35).…”
mentioning
confidence: 99%
“…Recent molecular analyses indicate that A. sulfurireducens (Crenarchaeota, Acidilobales) is a numerically dominant organism in acidic, high-temperature YNP springs (11,33), and closely related strains of Acidilobales have been detected in acidic terrestrial geothermal environments around the world (13,18,34). Previous microscopic analyses of batch cultures of A. sulfurireducens growing in pH 3.0 medium containing ␣-S 8 as the sole TEA indicated that the majority of cells were planktonic and not associated with large elemental sulfur particles during sulfurdependent growth (35).…”
mentioning
confidence: 99%
“…3a) and 1523vc, with short, rod-shaped cells, were found to affiliate with the genus Caldanaerobacter ( Table 2) and grew on proteins (␣-keratin, casein, and gelatin) and cellulose, respectively. Isolate 1507-2 possessed coccoid cells, grew on ␣-keratin or casein at 70°C and pH 6.0, and was found to be an archaeon of the Crenarchaeota phylum, representing a cluster of the so-called "unknown Desulfurococcales" (12,18). Isolates 1507-9 and 1521-1 had filamentous cells, occasionally forming clew-like structures ( Fig.…”
mentioning
confidence: 99%
“…DGGE with archaeal primers revealed the presence of noncultivated archaea in cellulose-degrading enrichments. Organisms present in cellulolytic enrichments 1521cmc and 1523rope represented a deep lineage in the Crenarchaeota phylum ("unknown Desulfurococcales"), to which many uncultured organisms from Yellowstone, Iceland, and Kamchatka hot springs were found to belong (10,12,18). The first cultivated organism of this group is "Fervidococcus fontis," isolated from Treshchinny Spring, Uzon Caldera (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies have documented the presence of a significant number of cultured and uncultured Crenarchaeota in Uzon Caldera thermal pools. It was reported that Crenarchaeota inhabited not only high-temperature springs (Wemheuer et al, 2013;Chernyh et al, 2015), but also springs with moderate temperatures (Perevalova et al, 2008;Burgess et al, 2012;Menzel et al, 2015). At the time of writing, many thermophilic and hyperthermophilic crenarchaeotes have been isolated from hot springs of Uzon Caldera, including members of genera Desulfurococcus (Bonch- Osmolovskaya et al, 1988;Perevalova et al, 2005;Kublanov et al, 2009), Thermoproteus (Bonch- Osmolovskaya et al, 1990), Acidilobus (Prokofeva et al, 2000;2009), Vulcanisaeta (Prokofeva et al, 2005), Fervidicoccus (Perevalova et al, 2010) and Pyrobaculum (Slobodkina et al, 2015).…”
mentioning
confidence: 99%